ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG KAPAL DENGAN METODE SERVQUAL DAN IPA - Ghina Dhiya Elok Sekar Putri; Renanda Nia Rachmadita; Gaguk Suhardjito (Proceeding Maritime Business Management Conference, 2024)
The ferry service company operates in sea transportation with several routes, including Surabaya – Balikpapan. The number of routes is directly linked to passenger volume, making it essential to ensure service quality meets passenger expectations. A decline in passenger numbers has been observed, mainly due to numerous complaints from company-conducted surveys. This decline in trust has caused passengers to switch to other operators. This study analyzes service gaps, determines acceptable service tolerance levels, and prioritizes necessary improvements. The SERVQUAL method assessed the gap between service performance and passenger expectations, showing negative gaps for 26 attributes. This indicates the company’s performance falls short of expectations. The Zone of Tolerance (ZOT) identified minimum acceptable service levels, with thresholds ranging from 0.10 to 1.36. Twenty-one attributes were below these thresholds. Importance Performance Analysis (IPA) was used to recommend service quality improvements by mapping attribute priorities in a Cartesian diagram. Seven attributes in Quadrant I were identified as top priorities for enhancement.